(untitled) (The Planet, 2022)
Aims: To compare serum lipid profiles immediately and random immediately on admission & 24 hours later in Acute myocardial infarction (AMII) patients. Methods: In this cross-sectional study, 118 AMI patients admitted in the Cardiology Department of a tertiary hospital in Bangladesh were evaluated. Serum total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and triglyceride (TG) were measured in both random states immediately other admission & then 24 hours later. Results: All the measured component of the lipid profile e.g.serum TC, HDL-C,LDCC and TG, were higher in the random post admission state then the measured components in 24 hours later in AMI patients. Conclusion: Random immediately after admission blood sample, which is more convenient, should be used for assessing lipid profile in AMI patients advised for the test.